Crusted Scabies In An HIV Seropositive Woman - Thappa Devinder Mohan; Laxmisha Chandrashekhar; Karthikeyan Kaliaperumal (Wolters Kluwer Medknow Publications, 2002)
A 27 year old female presented with itchy lesions over the trunk and extremities of six month duration. She had typical lesions of scabies in hands, besides crusted hyperkeratotic lesions over the lumber and gluteal areas, and was found to have underlying HIV infection. The case is reported for unusual presentation and its rarity.